Saoirene: enhanced the old - Azmi Nahar, Puteri Alisya Irdina; Yahya, Nur Sufi Fatihah; Mohd Fadly, Nur Adriana Afrina; Zainuddin, Zainina Syahirah Aleya (2024)
For this project, we decided to create jewellery pieces by utilising recycled materials. The national recycling rate of 35.38% in 2023, it is estimated that the amount of recyclable materials that was not recycled is 6.96%, or nearly one million tonnes (Datuk Ahmad Husaini, 2023). Our objective for this project is to demonstrate our commitment in reducing waste and protecting our natural environment for upcoming generations. To continue this project, materials were selected based on their durability and cost. Metal waste and plastic waste were used for our project. To recycle the metals for our project, they will be going through a melting process which is cost-effective. In summary, recycling waste into jewellery is both eco-friendly and cost-effective. It also can spark creativity. Recycled jewellery has a strong commercial potential that aligns with consumers beliefs and industrial trends.